School Principals Leadership and Teachersâ Stress Level in Malaysian Primary Schools - Yusof, Najeemah Mohd (EDUCARE, 2011)
ABSTRACT: Teaching is a profession that needs knowledge and the practice of psychological knowledge because this career relates directly to human. It is said that a long condition of stress could cause an individual to retreat from his/her work whether in physical or psychological way. Thus, a step to control the emotion was necessary for every individual. The purpose of this research was to investigate the leadership style of principals in relation to the stress level of teachers. The Leader Behaviour Description Questionnaire (LBDQ) measuring instrument was applied to measure the dimensions of principalsâ leadership style, initiating structure, and consideration. The teachersâ stress measuring instrument was used to measure the stress level of teachers based on principal leadership style. Sample consists of 200 teachers from Primary Schools in Malaysia. The data was analysed based on descriptive and inferential statistics. The findings showed that teachers had high opinion of principals. Moreover, there was a significant relationship between teachersâ stress level and the structural and consideration dimensions of the principalsâ leadership style. It was also discovered that the teacherâs stress level had an influence with the style of headmasterâs leadership. The factor that was identified as the main factor for work stress among the respondents was the discipline problem among student, this was followed by the factors of the restriction of time and source, appreciation factor, and interpersonal factor.KEY WORDS: School principal leadership, teachers, stress level, school leadership management, and human capital development.About the Author: Najeemah Mohd Yusof is a Lecturer at the School of Educational Studies USM (Science University of Malaysia), USM Campus, 1180 Minden, Pulau Penang, Malaysia. She can be reached at: najineen@usm.myHow to cite this article? Yusof, Najeemah Mohd. (2011). âSchool Principals Leadership and Teachersâ Stress Level in Malaysian Primary Schoolsâ in EDUCARE: International Journal for Educational Studies, Vol.4(1) August, pp.63-82. Bandung, Indonesia: Minda Masagi Press owned by ASPENSI in Bandung, West Java; and FKIP UMP in Purwokerto, Central Java, ISSN 1979-7877.Chronicle of the article: Accepted (June 17, 2011); Revised (July 19, 2011); and Published (August 17, 2011).